Communication types and uses of enterprise microblogging in a global IT services organisation - Williamson, Cari Jeanne Hartley (My University, 2013)
The purpose of this research was to gain a better understanding of microblogging in the context of the enterprise, and how the use of an enterprise microblogging (EMB) platform can facilitate internal organisational communication The research establishes why, how and in what form employees post messages on an EMB platform, with particular reference to the way in which the platform is used by employees to shape internal communication within a global IT services organisation. The methodology deployed in this research is that of qualitative, genre analysis and from the results the communicative genres of EMB within a global IT services organisation are derived. The findings showed that EMB messages were mainly in the form of text only, their main purpose was to transfer knowledge between users and engage in conversations. The content shared was often: general-business-related information found both in the public domain and within the organisation; updates as to what employees were busy doing; and employees’ opinions and suggestions across a broad set of work related topics. The platform was used to update people, transfer knowledge, voice opinions, engage in pleasantries and praise, have conversations that led to the resolution of specific problems, provide news flashes, notify others of things to come and provide clarity on previously shared information. What becomes evident from the comparison of the results with other case studies in this field of research is that the content, purpose and form of posts were not unique, but the frequency of the emerging genres was diverse and appeared to be dependent on the context and culture of the organisation under study.
MBA thesis
Keywords: Microblogging; Blogging; Information technology